Densification and crystallization of nonstoichiometric cordierite glass with excess MgO synthesized from kaolin and talc - Banjuraizah, Johar; Hasmaliza, Mohamad; Zainal Arifin, Ahmad. (The American Ceramic Society, 2011)
Link to publisher's homepage at http://onlinelibrary.wiley.com/